Structural, dielectric, and Mossbauer studies of multiferroic (1-x)PbFe0.5Nb0.5O3 - xPbCr0.5Nb0.5O3 solid solution ceramics obtained by usual sintering and by high-pressure synthesis. (12th March 2017) - Raevskaya, S. I.; Kubrin, S. P.; Pushkarev, A. V.; Olekhnovich, N. M.; Radyush, Yu. V.; Titov, V. V.; Malitskaya, M. A.; Zakharchenko, I. N.; Chen, H.; Chou, C.-C.; Raevski, I. P.
ABSTRACT: In the(1-x)PbFe0.5 Nb0.5 O3 - xPbCr0.5 Nb0.5 O3 (PFN-xPCN) ceramics fabricated by a usual solid state synthesis route the content of the pyrochlore phase increases dramatically with x, exceeding 50% for x = 0.3 composition. Synthesis under high (6 GPa) pressure enabled us to obtain perovskite PFN-xPCN ceramics, though for compositions with x ≥ 0.4 an admixture of the pyrochlore phase was still present. Both the pseudocubic lattice parameter and ferroelectric phase transition temperature decrease monotonically as x grows. The composition dependence of the antiferromagnetic phase transition temperature for PFN-xPCN is very similar to that in the PFN-PbMO3 (M-Ti, Zr, Sn) solid solution systems implying the lack of magnetic exchange between Fe 3+ and Cr 3+ ions.